The transformation of ordinal scale for parametric statistic analysis on dental health questionnaire - Adi Hapsoro (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Questioner Measurement is very customize, it means that researchers make very individual based on the aim of the research. Frequently, the results of questioner measurements are numeric rank and index or both of them. Numeric rank and index are categorical data. Beside of validity and reliability problems, they have analytical problems as well. So, they need transformation to scale type (ratio, interval) data in order to minimize their problems. Purpose: This article reviews the effectiveness of two type data transformation in dental health research measurement. reviews: There are two type data transformations, i.e. interval equivalency and sum of rating transformation method. Conclusion: Interval equivalency transformation method is more effective for the data come from index, and sum of rating transformation method is more effective for the data come from numeric rank.